Answer:
A, B and D are true statements.
Step-by-step explanation:
We are given a binomial expansion
![(x+y)^n=^nC_0x^ny^0+^nC_1x^{n-1}y^1+^nC_2x^{n-2}y^2+...........+^nC_nx^0y^n](https://tex.z-dn.net/?f=%28x%2By%29%5En%3D%5EnC_0x%5Eny%5E0%2B%5EnC_1x%5E%7Bn-1%7Dy%5E1%2B%5EnC_2x%5E%7Bn-2%7Dy%5E2%2B...........%2B%5EnC_nx%5E0y%5En)
![(x+y)^n=x^n+nx^{n-1}y+^nC_2x^{n-2}y^2+...........nxy^{n-1}+y^n](https://tex.z-dn.net/?f=%28x%2By%29%5En%3Dx%5En%2Bnx%5E%7Bn-1%7Dy%2B%5EnC_2x%5E%7Bn-2%7Dy%5E2%2B...........nxy%5E%7Bn-1%7D%2By%5En)
Now we will check each option
Option A: The coefficients of
and
both equal 1.
If we see first and last term of the expansion, This statement is true.
Option B: For any term
in the expansion, a + b = n.
Let we take 3rd term of expansion
Here, a=n-2 and b=2
If we do a+b = n-2+2=n
a+b=n is true statement.
Option C: For any term x^ay^b in the expansion, a - b = n.
Let we take 3rd term of expansion
Here, a=n-2 and b=2
If we do a-b = n-2-2=n-4≠n
a-b=n is false statement.
Option D: The coefficients of x^ay^b and x^by^a are equal.
If we take second term from beginning and last of the expansion.
![\text{Coefficient From beginning } nx^{n-1}y=n](https://tex.z-dn.net/?f=%5Ctext%7BCoefficient%20From%20beginning%20%7D%20nx%5E%7Bn-1%7Dy%3Dn)
![\text{From last } nxy^{n-1}=n](https://tex.z-dn.net/?f=%5Ctext%7BFrom%20last%20%7D%20nxy%5E%7Bn-1%7D%3Dn)
This statement true.